2019
DOI: 10.1007/s00493-019-3892-8
|View full text |Cite
|
Sign up to set email alerts
|

Nowhere Dense Graph Classes and Dimension

Abstract: Nowhere dense graph classes provide one of the least restrictive notions of sparsity for graphs. Several equivalent characterizations of nowhere dense classes have been obtained over the years, using a wide range of combinatorial objects. In this paper we establish a new characterization of nowhere dense classes, in terms of poset dimension: A monotone graph class is nowhere dense if and only if for every h 1 and every ε > 0, posets of height at most h with n elements and whose cover graphs are in the class ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Joret, Micek and Wiechert [17] have recently shown that for fixed t ≥ 3, d(t, h) grows exponentially with h. The best bound to date in the general case is due to Joret, Micek, Ossona de Mendez and Wiechert [16], where they prove:…”
Section: Connections With Structural Graph Theorymentioning
confidence: 98%
See 1 more Smart Citation
“…Joret, Micek and Wiechert [17] have recently shown that for fixed t ≥ 3, d(t, h) grows exponentially with h. The best bound to date in the general case is due to Joret, Micek, Ossona de Mendez and Wiechert [16], where they prove:…”
Section: Connections With Structural Graph Theorymentioning
confidence: 98%
“…However, an exponential upper bound was given in [16], and more recently, two groups have announced a polynomial upper bound on c h . Joret, Micek, Ossona de Mendez and Wiechert have shown how their results in [16] can be extended to obtain this conclusion. Meanwhile, Kozik, Krawczyk, Micek and Trotter [24] have a much more complicated argument which [17] showed that the c h ≥ 2h − 2.…”
Section: Planar Posets and Dimensionmentioning
confidence: 99%
“…Thus dim(P ) is the least positive integer d such that P has a realizer of size d. Accordingly, to establish an upper bound of the form dim(P ) d, the most natural approach is simply to construct a realizer of size d for P . However, in recent papers [8,9,12,13,14,15,16,21,23,28,30], another approach has been taken. Let Inc(P ) denote the set of ordered incomparable pairs of P .…”
Section: Notation Terminology and Background Materialsmentioning
confidence: 99%
“…Recently, a number of important results connecting dimension with structural graph theory have been proved [2,12,13,14,16,21,30]. In particular, the following generalization of Theorem 1.3 is proved in [30] (see [21] for an alternative proof and [13,16] for further extensions). Theorem 7.1.…”
Section: Connections With Graph Minorsmentioning
confidence: 99%
“…It was proved by Joret, Micek, Ossona de Mendez and Wiechert [12] that if P is a poset of height at most h, and the cover graph of P has weak (3h − 3)-coloring number at most k, then dim(P ) 4 k . For posets P of height h = 2, this implies that the dimension is at most 4 k , where k is the weak 3-coloring number of the comparability graph of P. This will be significantly improved in Section 2 (see Theorem 4).…”
Section: Introductionmentioning
confidence: 99%